Machine Translation in Scholarly Publishing: A Scoping Review - Ayeni, Philips; Kulczycki, Emanuel; Bowker, Lynne (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
English occupies a central position in scholarly publishing, but using a lingua franca for scholarly publishing has consequences for scholars, science, and society. For instance, non Anglophone researchers may need longer to read and write in English and may face more manuscript revisions and rejections, potentially leading to a lower volume of research output, which could negatively affect career advancement. To what extent can machine translation (MT) tools (e.g., Google Translate) help to support a more multilingual scholarly publishing ecosystem? To find out, we undertook a scoping review of the literature to investigate how MT tools are being used for multilingual scholarly publishing. Following a multilingual search in nine bibliographic databases, 875 papers were retrieved and screened, and 39 were included for closer investigation. Analysis reveals that MT tools are being actively developed, tested, applied, and evaluated in the context of scholarly publishing. However, at present, these tools are not displacing English from its central position; the main use of MT tools currently is to reduce the burden of publishing in English for scholars with limited English proficiency. This suggests that technology alone cannot create or sustain a multilingual scholarly publishing ecosystem. Hence, meaningful policies, in addition to improved MT tools and language resources, are needed to create a more linguistically diverse and equitable scholarly publishing landscape.